Interactions of Silicon With Essential and Beneficial Elements in Plants - Pavlovic, Jelena; Kostic, Ljiljana; Bosnic, Predrag; Kirkby, Ernest A.; Nikolic, Miroslav (Frontiers in Plant Science, 2021)
Silicon (Si) is not classified as an essential element for plants, but numerous studies have demonstrated its beneficial effects in a variety of species and environmental conditions, including low nutrient availability. Application of Si shows the potential to increase nutrient availability in the rhizosphere and root uptake through complex mechanisms, which still remain unclear. Silicon-mediated transcriptional regulation of element transporters for both root acquisition and tissue homeostasis has recently been suggested as an important strategy, varying in detail depending on plant species and nutritional status. Here, we summarize evidence of Si-mediated acquisition, uptake and translocation of nutrients: nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulfur (S), iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), boron (B), chlorine (Cl) and nickel (Ni) under both deficiency and excess conditions. In addition, we discuss interactions of Si-with beneficial elements: aluminium (Al), sodium (Na), and selenium (Se). This review also highlights further research needed to improve understanding of Si-mediated acquisition and utilization of nutrients and vice versa nutrient status-mediated Si acquisition and transport, both processes which are of high importance for agronomic practice (e.g. reduced use of fertilizers and pesticides).